Modern Photovoltaic Installation Connected to the Distribution and Transport Network - A. Lamkaddem; N. El Moussaoui; M. Rhiat; K. Kassmi; R. Malek (Current Overview on Science and Technology Research Vol. 5, 2022)
This chapter concerns research on photovoltaic (PV) installations connected to the electrical distribution and transport network, and these malfunction detection units. This work is based on the injection of a power of 16 KW, produced by a PV panel field, on the medium voltage electrical network (25 KV). In order to make the injection system relies on the network and to minimize power losses, we have interposed blocks that control the opening and closing of the power switches of the DC/AC converter and synchronize the phase, the amplitude, as well as the frequency of the voltage and the current, injected into the electrical network. The simulation results obtained show that the designed system detects the malfunction of the system on the network side (voltage dip, phase shedding, frequency fluctuation, imbalance of the three-phase system), on the field side of the PV panel (distrust of converters, etc.) and ensures the injection of electrical energy into the network during the operation of the PV generators.